The False Promise of Principled Negotiations - Victor Martinez Reyes (Journal of Global Initiatives, 2015)
For over two decades, the method of principled negotiation has been the dominant formative approach to negotiation. Its flagship book, Getting to Yes (Fisher & Ury, 1981; Fisher, Ury, & Patton, 1991) remains the standard presentation of the method. Getting to Yes promotes the method of principled negotiation as an all-purpose strategy of negotiation. The authors of Getting to Yes developed the method of principled negotiation as an alternative to positional bargaining. In this article, the author contends that the method of principled negotiation is not the all-purpose strategy of negotiation promised in Getting to Yes. Furthermore, the author contends that the method of principled negotiation is not a strategy of negotiation at all. In addition, the author contends that by persuading that principled negotiation is an all-purpose strategy Getting to Yes misleads negotiators, hinders the development of actual negotiation strategies, and leads to suboptimal results in many negotiations. In this paper, the author discusses the main concepts used in building the method of principled negotiation and shows that the method is built on incomplete definitions and erroneous assumptions. The author argues in favor of moving beyond the method of principled negotiation in order to find actual solutions to the challenges posed by different negotiations. Thus, the author proposes using a variety of strategies designed to achieve different goals, instead of trying to use, in every case, the “all-purpose” method/strategy of principled negotiation.